The Role of Islamic Jurisprudence and Comparative Jurisprudence in Developing the Rules of International Law: An Analytical Study in Light of the United Nations Charter and International Developments (Comprehensive Journal of Science, 2026)
This study aims to examine the role of Islamic jurisprudence and comparative jurisprudence in developing rules of international law in light of the United Nations Charter and international changes. The study adopts an analytical approach by examining Maqasid al-Sharia, exceptional circumstances, the doctrine of fundamental change of circumstances, implied and absolute powers, and international justice. The study concludes that Islamic jurisprudence provides an important basis for balancing treaty obligations with the removal of harm, while comparative jurisprudence contributes to critiquing and developing international legal rules. The study recommends strengthening justice, good faith, and legal limits on the powers of United Nations organs.
Keywords: Islamic jurisprudence, comparative jurisprudence, international law, United Nations Charter, international changes, international justice